O processo decisório em torno do fechamento e do realinhamento de bases militares domésticas dos Estados Unidos: o comportamento e o desempenho eleitoral dos deputados - Shenia Kellen de Lima (2012)
This dissertation aims to test the relation between the closure and realignment of the Unites States domestic military bases (BRAC) and the electoral performance of the members of the House of Representatives. The period under analysis is 1988 to 2006. Chapter 1 outlines the analytical model that guides this work, including the main concepts pertinent to the research question and the factors that, according to the literature, shape Congressmens behavior. Chapter 2 analyses the precedents to the Defense Base Realignment and Closure Act of 1988, and why Congress approved a law that limited its influence over the closure and realignment of bases. The first BRAC round is also analyzed in this chapter. Chapter 3 focuses on the Defense Base Realignment and Closure Act of 1990, as well as its implications for the BRAC decision making process and the behavior of Congressmen. It also tests the hypothesis referring to the interference of congressmen in the BRAC decision making process by analyzing the latters behavior during the BRAC rounds of 1991, 1993, 1995 and 2005. Chapter 4 tests the dominant hypothesis in the literature, which states the existence of a correlation between base closures and realignments with Congressmens electoral defeat, by examining the 1988-2006 period. A new interpretation on the relationship between the BRAC and the electoral results of incumbents in affected districts are also presented. In the closing arguments, the research results, as well as their theoretical and empirical implications, are analyzed.